Resilient Agrifood Systems Science Group: Evaluation Report - Palmieri, N.; Bennett, B.; Fakoya, K.; Meisner, C.; Molinari, M.M. (2024)
The CGIAR 2030 Research and Innovation Strategy sets priorities to deliver solutions for development through 33 initiatives across three interlinked action areas: Systems Transformation, Resilient Agrifood Systems (RAFS), and Genetic Innovation. The RAFS Science Group (SG) delivers on research priorities aimed at transforming agri-food systems to enable the most vulnerable to access affordable, sufficient, safe, and healthy diets through 15 initiatives. This RAFS SG evaluation report is one of three SG evaluation reports, adopting a forward-looking perspective for the next portfolio 2025-30.